Pendampingan Pengurusan Legalitas Usaha Berupa Nomor Induk Berusaha (NIB) Bagi UMKM di Desa Kebondalem, Kecamatan Bareng, Kabupaten Jombang - Moch. Nur Syamsi; Khansa Florensa Ervanto; Rahila Iftikhar; Nadhiya Hana Aushafina; Cendhy Rezky Adi Vitara; Mu’tasim Billah (Jurnal Informasi Pengabdian Masyarakat, 2023)
Kebondalem Village is one of the villages located in Bareng Sub-district, Jombang Regency, with 110 Micro, Small, and Medium Enterprises (MSMEs). In Kebondalem Village, the majority of the community perceives the process of obtaining permits and establishing business legality as difficult and time-consuming. Furthermore, MSMEs in the Kebondalem Village area still lack awareness of the importance of business legality, resulting in many MSMEs not having the necessary business legality, particularly the Business Identification Number (NIB). The Business Identification Number (NIB) is crucial for entrepreneurs as it serves as a permit for business operations and commercial activities. The process of obtaining or issuing the Business Identification Number (NIB) can be done through the Online Single Submission (OSS) system. The purpose of this community service activity is to educate MSME actors in Kebondalem Village on how to apply for business permits online using the Online Single Submission (OSS) system and ensure the legal recognition of their businesses, specifically through the use of the Business Identification Number (NIB). Using a door-to-door approach, this community service activity involves visiting the homes of each MSME in the Kebondalem Village area. The aim of this activity is to educate the community about the process of obtaining the Business Identification Number (NIB]